Evaluating the Diagnostic Performance of Prehospital Stroke Scales Across the Range of Deficit Severity: Analysis of the Prehospital Triage of Patients With Suspected Stroke Study. Issue 12 (21st October 2022) - Ganesh, Aravind; van de Wijdeven, Ruben M.; Ospel, Johanna M.; Duvekot, Martijne H.C.; Venema, Esmee; Rozeman, Anouk D.; Moudrous, Walid; Dorresteijn, Kirsten R.I.S.; Hensen, Jan-Hein; van Es, Adriaan C.G.M.; van der Lugt, Aad; Kerkhoff, Henk; et al.
Abstract : Background: The usefulness of prehospital scales for identifying anterior circulation large vessel occlusion (aLVO) in patients with suspected stroke may vary depending on the severity of their presentation. The performance of these scales across the spectrum of deficit severity is unclear. The aim of this study was to evaluate the diagnostic performance of 8 prehospital scales for identifying aLVO across the spectrum of deficit severity. Methods: We used data from the PRESTO study (Prehospital Triage of Patients With Suspected Stroke Symptoms), a prospective observational study comparing prehospital stroke scales in detecting aLVO in suspected stroke patients. We used the National Institutes of Health Stroke Scale (NIHSS) score, assessed in-hospital, as a proxy for the Clinical Global Impression of stroke severity during prehospital assessment by paramedics. We calculated the sensitivity, specificity, positive predictive value, negative predictive value, and the difference in aLVO probabilities with a positive or negative prehospital scale test (ΔPaLVO ) for each scale for mild (NIHSS 0–4), intermediate (NIHSS 5–9), moderate (NIHSS 10–14), and severe deficits (NIHSS≥15). Results: Among 1033 patients with suspected stroke, 119 (11.5%) had an aLVO, of whom 19 (16.0%) had mild, 25 (21.0%) had intermediate, 30 (25.2%) had moderate, and 45 (37.8%) had severe deficits. The scales had low sensitivity and positive predictive value in patients with mild-intermediate deficits, and poor specificity, negative predictive value, and accuracy with moderate-severe deficits. Positive results achieved the highest ΔPaLVO in patients with mild deficits. Negative results achieved the highest ΔPaLVO with severe deficits, but the probability of aLVO with a negative result in the severe range was higher than with a positive test in the mild range. Conclusions: Commonly-used prehospital stroke scales show variable performance across the range of deficit severity. Probability of aLVO remains high with a negative test in severely affected patients. Studies reporting prehospital stroke scale performance should be appraised in the context of the NIHSS distribution of their samples.